2019
DOI: 10.3906/vet-1803-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, enzymatic, and antioxidant enrichments of full-fat soybean and sunflower meal by Bacillus subtilis (ATCC® 6633™) fermentation using a solid-state bioreactor

Abstract: In 2016, the world's soybean meal production reached 217 million tones and nearly half of it was used as protein supplement in farm animal nutrition (1). Sunflower meal (SFM), the fourth largest oilseed meal produced in the world, also serves as a protein source, mostly in ruminant diets, while its use in poultry and pig diets is limited (2). Chemical composition of these plant meals determines their levels in complete feeds fed to farm animals. For instance, soybean and its by-products may contain appreciable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
7
0
3
Order By: Relevance
“…spp., fermentations, similar to our results. Furthermore, Karakurt et al, (2019) demonstrated clearly that fixing pH at around 5.5 for Bacillus subtilis fermentation of both sunflower and soybean meal samples produced an appreciable amount of organic acids in the form of acetate, butyrate and lactate, similar to the results of pH and organic acids obtained from both moisture levels at 48 and 72 h of fermentation in our experiment.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…spp., fermentations, similar to our results. Furthermore, Karakurt et al, (2019) demonstrated clearly that fixing pH at around 5.5 for Bacillus subtilis fermentation of both sunflower and soybean meal samples produced an appreciable amount of organic acids in the form of acetate, butyrate and lactate, similar to the results of pH and organic acids obtained from both moisture levels at 48 and 72 h of fermentation in our experiment.…”
Section: Resultssupporting
confidence: 88%
“…In these studies, it was demonstrated that the ratio of added water to solid materials in SSF is crucial for improved metabolic activity of microorganism, and directly interacts together with oxygen for the removal of heat generated during the fermentation. In SSF, the water content of fermenting substrate is preferable above 60%, and moreover the optimal level of water content in SBM fermentation studies ranged from 75 to 85% water content (Amadou et al, 2010;Yasar et al, 2018;Karakurt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of microbial growth was parallel to the pattern of CO2 production which was the highest at 24 hr (1% in AO, 4% in C+D, 6% in LBS and 4% in SC), thereby gradually decreased. Furthermore, organic acids produced by microbial fermentation such as lactic acid in our study (Table 2) have a negative impact on microbial growth by 48 hr fermentation (Karakurt et al, 2019). In general, the efficacy of fermentation can greatly be influenced by the type of microorganism used, temperature, pH and the rates of aeration and stirring (Krishna, 2005).…”
Section: Monitoring Fermentation Parametersmentioning
confidence: 84%
“…The conditions of temperature, pH, pressure and stirring in microbial fermentation are milder than that of a heat or chemical treatment wherein harsh conditions of food processing may cause undesirable Maillard reaction, yielding oxidised forms of amino acids (Sarwar Gilani et al, 2012). On the other hand, optimising pH, stirring rate, moisture level and temperature depending on the type and strain of microorganisms used and the expected outcome at the end of fermentation greatly affects the efficacy of microbial solid state fermentation using modern bioreactor (Yasar and Tosun, 2018;Karakurt et Open Access al., 2019). However, microbial fermentation is not always expected to result in both adding functionalities and causing nutritional fortifications.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies reporting decreased crude fibre and its fractions by the solid-state fermentation (Lateef et al, 2008;Yasar and Tosun, 2018c;Karakurt et al, 2019). Altop et al (2018) reported that the starch and sugar content of industrial by-products were reduced as a result of fungal fermentation.…”
Section: Resultsmentioning
confidence: 99%